Dissolved organic phosphorus enhances arsenate bioaccumulation and biotransformation in Microcystis aeruginosa. (September 2019) - Wang, Zhenhong; Gui, Herong; Luo, Zhuanxi; Zhen, Zhuo; Yan, Changzhou; Xing, Baoshan
Abstract: Only limited information is available on the effects of dissolved organic phosphorus (DOP) on arsenate ( As (V)) bioaccumulation and biotransformation in organisms. In this study, we examined the influence of three different DOP forms (β-sodium glycerophosphate (βP), adenosine 5′-triphosphate (ATP), and D-Glucose-6-phosphate disodium (GP) salts) and inorganic phosphate (IP) on As (V) toxicity, accumulation, and biotransformation in Microcystis aeruginosa. Results showed that M. aeruginosa utilized the three DOP forms to sustain its growth. At a subcellular level, the higher phosphorus (P) distribution in metal-sensitive fractions (MSF) observed in the IP treatments could explain the comparatively lower toxic stress of algae compared to the DOP treatments. Meanwhile, the higher MSF distribution of arsenic ( As ) in M. aeruginosa in the presence of DOP could explain the higher toxicity with lower 96-h half maximal effective concentration (EC50 ) values. Although we observed As (V) and P discrimination in M. aeruginosa under IP treatments with high intracellular P/ As, we did not find this discrimination under the DOP treatments. As accumulation in algal cells was therefore greatly enhanced by DOP, especially βP, given its lower transformation rate to phosphate compared to ATP and GP in media. Additionally, As (V) reduction and, subsequently, As (III) methylation were greatly facilitated in M. aeruginosa by the presence of DOP, particularly GP, which was confirmed by the higher relative expression of its two functional genes ( arsC and arsM ). Our findings indicate that As (V) accumulation and its subsequent biotransformation were enhanced by organic P forms, which provides new insight into how DOP modulates As metabolism in algae. Graphical abstract: Image 1 Highlights: M. aeruginosa could utilize the three DOP to sustain its growth. As(V) and P aren't discriminated by M. aeruginosa under DOP conditions. Arsenic accumulation were enhanced under DOP conditions especially βP. As (V) reduction and subsequent methylation was facilitated by DOP, particularly GP. Higher MSF of As can explain higher toxicity on algae under DOP conditions.